Putting Problematization to the Test of Our Present. (March 2021) - Stengers, Isabelle
At the end of his life, Michel Foucault wrote of 'problematization' as what he had done all along. Yet some commentators see a 'new' Foucault emerging together with this term. This essay accepts the last hypothesis and connects it with the French scene, where problematization was already familiar, and its use under tension. Starting with Bachelard, problematization was related with a polemic epistemological stance, but its reprise by Gilles Deleuze turned it into an affirmative theme dramatizing the creation of problems. Situating Foucault's problematization in this philosophical line permits us to develop the relation he proposed between problematization and the test of contemporary reality on the thinker. This paper will put problematization itself to the test of our present, that is, to the prospect of the social-ecological devastation associated with climate disorder. Both following and betraying Foucault with the help of Whitehead and Haraway, problematization will then be related to the power of sensible events, a power which requires allowing oneself to be touched, and allowing what touches us the power to modify the relation we entertain to our own reasons.